Comparison of liver gene expression by RNAseq and PCR analysis after 8 weeks of feeding soy protein isolate- or casein-based diets in an obese liver steatosis rat model. Issue 12 (8th November 2019) - Kozaczek, Melisa; Bottje, Walter; Greene, Elizabeth; Lassiter, Kentu; Kong, Byungwhi; Dridi, Sami; Korourian, Soheila; Hakkak, Reza
Abstract : Differential expression of genes provides insight into fundamental mechanisms associated with the ability of soy protein isolate to attenuate liver steatosis in genetically obese rats. Abstract : Previously, we reported that feeding soy protein isolate (SPI) reduced liver steatosis in obese rats compared to those fed a casein (CAS)-based diet; however, the mechanism for this protection is unknown. To gain insight into the ability of SPI to ameliorate liver steatosis, we conducted transcriptomic (RNAseq) analysis on liver samples from obese rats fed either the SPI- or CAS-based diets ( n = 8 per group) for 8 weeks using an Ilumina HiSeq with 100 base paired end reads for sequencing. Data were analyzed by Ingenuity Pathway Analysis (IPA) software using a P < 0.05 and 1.3-fold differential expression cutoff values between the SPI- and CAS-based groups. To independently validate the RNAseq data, we conducted targeted mRNA expression analysis using quantitative PCR (qPCR) on a subset of differently expressed genes. The results indicate that mRNA expression by qPCR concurred with RNAseq for NPTX2, GPT, INMT, and HAL that were up-regulated in SPI-fed rats ( P < 0.05) and PRSS8, AJUBA, CSF2RB, and Cyp2c12 that were down-regulated ( P < 0.05) in SPI-fed rats compared to CAS-fed rats. Our findings may shed light on understanding mechanisms enabling SPI diet to reduce liver steatosis in this obese Zucker rat model.